(untitled) (Eurasian Journal of Ecology, 2016)
The anatomical characteristic of Stipa capillata L. the dominant kind ofplants of territory of semipalatinsk test site is given. Af increase of PED there is an increase of quantitative parameters in structure of overground and underground organs. The greatest accumulation of radioactive elements is revealed in near root soil and underground organs.